A study of the undergraduate library science programs in selected library schools in Metro Manila with implications on the education of information professionals and curriculum development - Madrid, Jennifer M.; Cruz, Ma. Divina P.; Tayona, Linda M. (Quezon City : Institute of Library Science, University of the Philippines Diliman, 1999)
This is a study of the undergraduate library science programs in selected library schools in Metro Manila. Its objectives are: 1) determine the present curricular offerings in selected library schools in Metro Manila; 2) find out the effectiveness and relevance of the library science programs as perceived by: a) library science graduates in terms of their present job; b) library administration in the government and private institutions in relation to their library's needs for information professionals; c) dean/heads of library schools in terms of producing information professionals; 3) determine the expectations of the library administrators in government and private institutions in terms of qualifications of library science graduates; and 4) offer suggestions and recommendations to respond to employment needs and for the improvement of information professionals.
This study is descriptive in nature and used of the survey method, specifically, the cross-sectional survey. The study has three groups of respondents: library science graduates; library administrators and heads/dean of library science schools. Two separate questionnaires were used to record the answers of the library science graduates and library administrators. An interview guide was prepared for the heads/dean of library science schools. The curricula of the library schools were collected. Each subject in the curriculum was listed and compared with those of the other curricula. Furthermore, conclusions were drawn accordingly.
The study concludes that: 1) the curricular offerings in selected library schools studied are tailored toward producing librarians but gradually changing toward producing information professionals; 2) most of the library science graduates believe that the knowledge and training they had in school is sufficient in terms of answering the needs in their present jobs; 3) most of the library administrators indicate that library science subjects in the present curriculum are still very important based on the needs and activities of their respective libraries; 4) the dean/heads of library schools are aware that there is still room for improvement in the areas of facilities/equipment for the program, and method of administering these courses; 5) most of the library administrators say that a bachelor's degree in library and information science is adequate to get a librarian's job but a lot still needs to be done. One should continue to keep acquiring new skills and knowledge by pursuing graduate studies and/or attending training programs, seminars, and workshops; and, 6) libraries and information centers in the government and private sectors need librarians and information professionals who can handle the information needs of their constituents. The librarians and information professionals should possess the knowledge and training to deal with the tasks assigned to them.
Computer print out.
Vita.
Thesis (Master of Library and Information Science)--University of the Philippines Diliman
Keywords: Library schools -- Philippines -- Manila Metropolitan Area -- Curricula; Library education -- Philippines -- Manila Metropolitan Area